Risk factors of Ganciclovir‐related neutropenia after allogeneic stem cell transplantation: a retrospective monocentre study on 547 patients. (22nd April 2013) - Venton, G.; Crocchiolo, R.; Fürst, S.; Granata, A.; Oudin, C.; Faucher, C.; Coso, D.; Bouabdallah, R.; Berger, P.; Vey, N.; Ladaique, P.; Chabannon, C.; et al.
Abstract Cytomegalovirus (CMV) infection is a serious complication that may occur in the weeks or months following bone marrow transplantation. However, both Ganciclovir and the CMV infection itself can cause marrow toxicity, notably neutropenia, that may consequently expose these immunosuppressed patients to life‐threatening bacterial and/or fungal infections. The aim of this retrospective study was to identify factors associated with the occurrence of grade III–IV neutropenia among patients receiving pre‐emptive Ganciclovir therapy after allogeneic stem cell transplantation at our Institution. We identified 547 consecutive patients transplanted from January 2005 to June 2011 at our Institution. In all, 190 patients (35%) presented with CMV reactivation of whom 30 patients (5%) were excluded from the analysis because they already had neutropenia at the time of reactivation. Finally, 160 (29%) patients were analysed. According to multivariate analysis, at the time of treatment initiation, the risk factors significantly associated with a grade III–IV Ganciclovir‐related neutropenia included a high viral load (hazard ratio (HR) = 2.68, 95% CI 1.25–5.737, p 0.01); an absolute neutrophil count >3000 was a protective factor (HR = 0.26, 95% CI 0.125–0.545, p <0001) whereas serum creatinine >2 mg/dL was associated with higher Ganciclovir‐related neutropenia (HR = 2.4, 95% CI 1.11–5.17, p 0.002). This large analysis revealed three risk factors for Ganciclovir‐related neutropenia among patients with CMV reactivation after allogeneic stem cell transplantation; prompt identification of patients at risk when antiviral therapy is started may allow clinicians to adopt adequate preventive measures, so reducing the morbidity and mortality associated with CMV reactivation.